Prendersi ‘gentilmente’ sul serio. Un’intima curvatura riflessiva sull’etnografia nella lotta e la co-costruzione di intenzionalità sul campo - Sabina Tosi Cambini (Archivio Antropologico Mediterraneo)
This contribution applies a reflexive approach to my diversified fieldworks carried out in some contexts that policies, social sciences and civil society call ‘marginal’ – albeit moved by very different perspectives and intentions –, bringing out the demand of people towards the anthropologist to be able to develop a ‘gentle’ relationship, capable of ‘culturally’ taking into account their biographies and their social ‘position’ without trapping them either in the first or in the second; and, therefore, investigating the meso and macro structural aspects of this positioning as well as their search for a 'good life'. These two aspects have been kept constantly connected also in the applied tension of the discipline, which for many aspects and years has also been inseparable from my ethnographic research. Staying inside people's life contexts to understand them and 'act' with them, has also made projects 'flesh': taking their daily lives 'seriously', their hesitations, fears, discontinuities, permanent uncertainty, the intentionality of the anthropologist and of the subjects has changed over time and reciprocally – since the people themselves have taken my proposals 'seriously' –, co-constructing the intentionality itself through paths that are anything but linear. Starting from some 'points of support' deriving from the discussion around dark anthropology and the anthropology of the good (and of resistance), the text develops through cross-references between different times and fieldworks, intertwining biography and ethnography, so the contexts can reverberate in the anthropological reflection. The housing issue is the thread that leads us to the self-recovery building projects, through a path in which intentionality – in this text as in the fieldwork – is (re)generated and repositioned inside the relationship.